STATE OF PATIENT SAFETY CULTURE IN BULGARIA: A LITERATURE REVIEW - Rositsa T. Dimova; Ilian Y. Doykov; Lyuboslav R. Dimov (Journal of IMAB, 2018)
This paper aimed to review and analysis of current literature, based on the complex evaluation of the publications in the available national and international literature, related to hospital patient safety culture. >A literature review was conducted via searching the MEDLINE, PubMed, Google Scholar and Sofia Central Medical Library electronic databases. Relevant publications were also retrieved from the paper-based collection at the Medical University in Plovdiv, using the “de visu” approach. "Patient safety", "safety culture", "hospital safety culture", "prevention of medical errors", "patient safety reporting system" and "medical error" served as search keywords. The study selection identified a total of 224 surveys. Finally, only 21 articles were examined and discussed in the review. The current literature review shows the need to develop and maintain a positive patient safety culture in the healthcare settings in Bulgaria. It requires amendments to the existing regulations, the introduction of uniform taxonomy, universal measuring instruments of patient safety culture and registration of medical errors in healthcare settings.